Passion Isn't Always a Good Thing: Examining Entrepreneurs' Network Centrality and Financial Performance with a Dualistic Model of Passion - Ho, Violet T.; Pollack, Jeffrey M. (Journal of Management Studies, 2014)
AbstractWe propose a conceptual model that links entrepreneurs' passion, network centrality, and financial performance, and test this model with small business managers in formal business networking groups. Drawing on the dualistic model of passion, we explore the relationships that harmonious and obsessive passion have with financial performance, mediated by network centrality. Results indicate that harmoniously passionate entrepreneurs had higher out‐degree centrality in their networking group (i.e., they were more inclined to seek out members to discuss work issues), which increased the income they received from peer referrals and, ultimately, business income. Obsessively passionate entrepreneurs had lower in‐degree centrality (i.e., they were less likely to be approached by peers), and in turn received less income from referrals and less business income. These findings highlight that entrepreneurial passion does not always result in positive financial outcomes – the type of passion makes a difference. Implications for research and practice are discussed.